2016
DOI: 10.1177/0731948716649754
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of Virtual and Concrete Manipulatives to Teach Algebra to Secondary Students With Learning Disabilities

Abstract: A sizable body of literature exists studying various technologies and pedagogical practices for teaching secondary mathematics curriculum to students with a learning disability in mathematics. However, with the growing footprint of computer-based technologies in today's classrooms, some areas of study, such as the use of virtual manipulatives, lack sufficient exploration. Although concrete manipulatives were studied for many decades for students with a learning disability and are considered a best practice, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
114
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(123 citation statements)
references
References 22 publications
9
114
0
Order By: Relevance
“…A total of 89 students who were identified as having LD took part across the 12 studies. Studies reported their identification criteria for LD using two different approaches: the IQ‐achievement discrepancy model in three studies (Hunt & Vasquez, 2014; Hutchinson, 1993; Satsangi et al., 2016) and school districts’ RTI processes in three studies (Satsangi et al., 2016; Satsangi, Hammer, & Evmenova, 2018; Satsangi, Hammer, & Hogan, 2018). Three studies (Maccini & Hughes, 2000; Scheuermann, Deshler, & Schumaker, 2009; Strickland & Maccini, 2013a) reported that the schools’ processes followed each state's guidelines, yet did not provide detailed information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 89 students who were identified as having LD took part across the 12 studies. Studies reported their identification criteria for LD using two different approaches: the IQ‐achievement discrepancy model in three studies (Hunt & Vasquez, 2014; Hutchinson, 1993; Satsangi et al., 2016) and school districts’ RTI processes in three studies (Satsangi et al., 2016; Satsangi, Hammer, & Evmenova, 2018; Satsangi, Hammer, & Hogan, 2018). Three studies (Maccini & Hughes, 2000; Scheuermann, Deshler, & Schumaker, 2009; Strickland & Maccini, 2013a) reported that the schools’ processes followed each state's guidelines, yet did not provide detailed information.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the participants included 30 Caucasians, eight African Americans, and six Hispanics; 45 were not identified. Only three studies explicitly reported the participants’ socioeconomic status (SES; Hunt & Vasquez, 2014; Maccini & Hughes, 2000; Satsangi et al., 2016). In three studies, five out of 12 students qualified for free or reduced‐price lunch or were of below average SES.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two interventions by another research group, Satsangi & Bouck (2015) and Satsangi et al (2016) took an entirely different approach. Both studies examined whether students with a mathematics disability could benefit from learning about geometry using virtual, computer-based manipulatives - both compared to no intervention and to physical manipulatives (the physical manipulatives were slightly more effective.)…”
Section: Resultsmentioning
confidence: 99%
“…Rather, what we need to know is which kinds of presentations we should use. One recent study, Kennedy et al (2015), did compare different kinds of multimedia presentations, and another (Satsangi et al, 2016) compared virtual and physical presentations of the same objects.…”
Section: Resultsmentioning
confidence: 99%